Odpowiedź:
a.
[tex] - 3x = 17 - 5[/tex]
[tex] - 3x = 12[/tex]
[tex]x = - 4[/tex]
b.
[tex]3(1 - x) + 2 = - 7[/tex]
[tex]3 - 3x + 2 = - 7[/tex]
[tex] - 3x = - 3 - 2 - 7[/tex]
[tex] - 3x = - 12[/tex]
[tex]x = 4[/tex]
c.
[tex]3(0.4x + 1.2) - 2(0.3x - 2.6) = 0.1x[/tex]
[tex]1.2x + 3.6 - 0.6x + 5.2 = 0.1x[/tex]
[tex]1.2x - 0.6x - 0.1x = - 3.6 - 5.2 \\ 0.5x = - 8.8 \\ x = - 17.6[/tex]
d .
[tex]3x(2x + 5) = (x + 3)(6x + 1) \\ 6 {x}^{2} + 15x = 6 {x}^{2} + x + 18x + 3 \\ 15x - x - 18x = 3 + 6 {x}^{2} - 6 {x}^{2} \\ - 4x = 3 \\ x = \frac{3}{4} [/tex]
e.
[tex]2x + 44 = 12y + 1 \\ 2x - 12y = 1 - 44 \\ 2x - 12y = - 43[/tex]